Copper(i)–Y zeolite catalyzed N-sulfonylketenimine mediated annulation of hydroxynaphthoquinones: syntheses of naphtho[2, 1-b]furan-2, 5-diones and benzo[de]chromene-2, 6-diones. Issue 54 (16th June 2016) - Ramanathan, Devenderan; Namitharan, Kayambu; Pitchumani, Kasi
Abstract : An efficient, one pot synthesis of novel naphtho[2, 1- b ]furan-2, 5-diones and benzo[ de ]chromene-2, 6-diones was reported using copper(i )–Y zeolite as catalyst. Abstract : An efficient one pot synthesis for the construction of novel naphtho[2, 1- b ]furan-2, 5-diones and benzo[ de ]chromene-2, 6-diones using copper(i )–Y zeolite catalyzed reaction of N -sulfonylketenimine with 2-hydroxy-1, 4-naphthoquinone and 5-hydroxy-1, 4-naphthoquinone followed by the elimination of p -toluenesulfonamide is reported. The intermediate N -sulfonylketenimine, generated by (3+2) cycloaddition/ring-opening reaction/retro-Wolff rearrangement, cascade, and annulation, promotes the reaction involving the inter- and intramolecular nucleophilic addition/dehydration followed by hydrolysis and elimination of p -toluenesulfonamide to afford the target products in good yield.